KESIAPAN SUMBER DAYA MANUSIA DALAM MENJALANKAN PROGRAM KOPERASI DESA MERAH PUTIH: SEBUAH TEROBOSAN PEMERINTAH UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT DESA - Rinaldi, Oktavian; Saladin, Tomy; Munawaroh, Mumun; Faoziyah, Sitti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Red and White Village Cooperative (Koperasi Desa Merah Putih) is a strategic government program designed to strengthen the economic resilience of rural communities based on the values of mutual cooperation and the ideology of Pancasila. Although its implementation has been reinforced through Presidential Instruction Number 9 of 2025, the program continues to face various challenges, particularly regarding the readiness of human resources (HR) responsible for managing the cooperatives. This study aims to describe the level of readiness of cooperative managers in developing cooperative business units and to analyze the support provided by village governments in strengthening cooperative institutions. Employing a qualitative descriptive approach, data were collected through in-depth interviews and documentation involving six cooperative managers from three villages in Balongan District, Indramayu Regency. The findings reveal that the managers demonstrate a strong commitment to operating the cooperatives and recognize their importance for the local economy. However, their understanding of cooperative principles, business management, institutional regulations, and digitalization remains limited. In addition, technical competencies related to administration, bookkeeping, and operational management are still inadequate. Despite these limitations, the managers show readiness to develop business programs when supported through training, mentoring, and facilitation from village governments and relevant institutions. The study also highlights that experience plays a crucial role in enhancing cooperative governance, particularly in decision-making, partnership development, and conflict resolution. Overall, limited human resource capacity remains the primary obstacle to the development of the Red and White Village Cooperative, underscoring the need for managerial training, technical assistance, and practice-based capacity-building programs to ensure its sustainability as an instrument of rural economic empowerment.